The predictive validity for mortality of the driving pressure and the mechanical power of ventilation - David M. P. van Meenen; Ary Serpa Neto; Frederique Paulus; Coen Merkies; Laura R. Schouten; Lieuwe D. Bos; Janneke Horn; Nicole P. Juffermans; Olaf L. Cremer; Tom van der Poll; Marcus J. Schultz; for the MARS Consortium (Intensive Care Medicine Experimental, 2020)
Abstract Background Outcome prediction in critically ill patients under invasive ventilation remains extremely challenging. The driving pressure (ΔP) and the mechanical power of ventilation (MP) are associated with patient-centered outcomes like mortality and duration of ventilation. The objective of this study was to assess the predictive validity for mortality of the ΔP and the MP at 24 h after start of invasive ventilation. Methods This is a post hoc analysis of an observational study in intensive care unit patients, restricted to critically ill patients receiving invasive ventilation for at least 24 h. The two exposures of interest were the modified ΔP and the MP at 24 h after start of invasive ventilation. The primary outcome was 90-day mortality; secondary outcomes were ICU and hospital mortality. The predictive validity was measured as incremental 90-day mortality beyond that predicted by the Acute Physiology, Age and Chronic Health Evaluation (APACHE) IV score and the Simplified Acute Physiology Score (SAPS) II. Results The analysis included 839 patients with a 90-day mortality of 42%. The median modified ΔP at 24 h was 15 [interquartile range 12 to 19] cm H2O; the median MP at 24 h was 206 [interquartile range 145 to 298] 10−3 J/min/kg predicted body weight (PBW). Both parameters were associated with 90-day mortality (odds ratio (OR) for 1 cm H2O increase in the modified ΔP, 1.05 [95% confidence interval (CI) 1.03 to 1.08]; P < 0.001; OR for 100 10−3 J/min/kg PBW increase in the MP, 1.20 [95% CI 1.09 to 1.33]; P < 0.001). Area under the ROC for 90-day mortality of the modified ΔP and the MP were 0.70 [95% CI 0.66 to 0.74] and 0.69 [95% CI 0.65 to 0.73], which was neither different from that of the APACHE IV score nor that of the SAPS II. Conclusions In adult patients under invasive ventilation, the modified ΔP and the MP at 24 h are associated with 90 day mortality. Neither the modified ΔP nor the MP at 24 h has predictive validity beyond the APACHE IV score and the SAPS II.